Prediction of Depth-Induced Stress Distribution and Maintenance Cost Implications for Submerged Structural Components - Ekperi Nelson Ibezim; Akpuh Davidson (International Journal of Fracture Mechanics and Damage Science, 2025)
This study investigates the influence of water depth on stress distribution and structural integrity of submerged mechanical components . Structural models fabricated from mild steel, stainless steel, carbon steel, and copper alloy were examined under hydrostatic loading corresponding to water depths between 30 cm and 150 cm. Results indicate that normal and shear stresses increased proportionally with depth due to intensified hydrostatic pressure. Mild steel exhibited the highest stress concentrations, whereas stainless steel demonstrated superior resistance to deformation. Stress intensification was pronounced around sharp corners, holes, and geometric discontinuities. The study also assessed maintenance and operational cost implications by incorporating analytical expressions for Total Gross Margin (TGM), Scrap Disposal Cost per Incident (SDCPI), and Total Breakdown Maintenance Cost (TBdMc). Findings reveal that deeper installations incur higher structural stress and potentially higher maintenance costs due to increased likelihood of fatigue and localized failure. The research provides guidance for material selection, geometric optimization, and lifecycle cost assessment for underwater mechanical systems such as pipelines, braces, and submerged pressure vessels. Analytical formulations are complemented by numerical simulations to capture nonlinear stress variations and localized stress concentrations under varying hydrostatic pressures. The predicted stress profiles are further linked with degradation and damage accumulation models to estimate inspection frequency, repair requirements, and component service life. Based on these estimates, a maintenance cost assessment model is developed to evaluate the economic implications of operating at greater depths. Results indicate that increasing depth significantly amplifies stress gradients, leading to higher fatigue and corrosion risks, which in turn escalate maintenance frequency and lifecycle costs. The study highlights the importance of depth-aware design and predictive maintenance strategies in optimizing both structural reliability and long-term operational costs of submerged systems.
Keywords: finite element modeling; hydrostatic loading; maintenance cost modeling; stress distribution; submerged structures; water depth